Port Risk Mitigation with FMEA Method on Port Operational Information System at PT. Pelindo (Persero) Sibolga Branch: Case Study at Port of Sibolga - Novita Jambak, Indah; Kurniawan R, Rakhmat (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2025)
Port operations face challenges in the form of potential risks such as delays in data recording, data inconsistencies between units, and lack of system integration that can hinder logistics distribution. This study identified 20 potential operational risks using the Failure Mode and Effect Analysis (FMEA) method to help map mitigation priorities through the calculation of the Risk Priority Number (RPN). The results of the risk mapping were used as a basis for designing the functional requirements of a web-based port operational information system. The system was developed using PHP, Laravel, and MySQL to support structured recording of loading and unloading activities, ship scheduling, and logistics monitoring. Although the RPN values were used to understand risk priorities, they did not directly determine the system features. Instead, the risk analysis served to provide an overall understanding for designing a system that better matches operational needs. The validation of system benefits at this stage remains conceptual, and future implementation is needed to test its effectiveness in actual port operations.